Negotiating better teamwork. Part two, role description and feedback form - Collins, William, active 2024; Yue, Tao, active 2024 (London : Rotterdam School of Management, Erasmus University, 2024)
Alex, Bobby, Chris, Dale, Eden, Frankie, and Gale are members of an MBA program team with various personalities and challenges. Each member has their own unique perspective and issues within the team dynamics. They approach Lee, the team leader, seeking his understanding, support, or cooperation to address their individual concerns and conflicts within the team.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Teams in the workplace -- Case studies